A soldier of shadows - Forrest, Bella (Forrest, Bella. Shade of vampire, 2015)
"The vision Benjamin had of himself as an infant could hold the answers he desperately seeks. Answers about his past. Answers that are key to solving his dilemma in the present" -- back cover.